Tmem2 restricts atrioventricular canal differentiation by regulating degradation of hyaluronic acid. Issue 12 (10th September 2019) - Hernandez, Lydia; Ryckebüsch, Lucile; Wang, Carole; Ling, Rachel; Yelon, Deborah
Abstract: Background: Atrioventricular valve development relies upon the precisely defined dimensions of the atrioventricular canal (AVC). Current models suggest that Wnt signaling plays an important role atop a pathway that promotes AVC development. The factors that confine AVC differentiation to the appropriate location, however, are less well understood. Results: Transmembrane protein 2 (Tmem2) is a key player in restricting AVC differentiation: in zebrafish, t mem2 mutants display an expansion of AVC characteristics, but the molecular mechanism of Tmem2 function in this context remains unclear. Through structure‐function analysis, we demonstrate that the extracellular portion of Tmem2 is crucial for its role in restricting AVC boundaries. Importantly, the Tmem2 ectodomain contains regions implicated in the depolymerization of hyaluronic acid (HA). We find that tmem2 mutant hearts exhibit excess HA deposition alongside broadened distribution of Wnt signaling. Moreover, addition of ectopic hyaluronidase can restore the restriction of AVC differentiation in tmem2 mutants. Finally, we show that alteration of a residue important for HA depolymerization impairs the efficacy of Tmem2 function during AVC development. Conclusions: Taken together, our data support a model in which HA degradation, regulated by Tmem2, limits the distribution of Wnt signaling and thereby confines the differentiation of the AVC. Key Findings: The Tmem2 ectodomain is critical for restricting AVC differentiation. Tmem2 limits the extent of Wnt signaling activity at the AVC. Tmem2 confines AVC differentiation by promoting HA degradation.